The Effect of Type II Diabetes Mellitus on Some Prostate Markers in Iraqi Men - Khalid Maseer Rmaidh (Journal of Global Pharma Technology, 2016)
Aim: Diabetes mellitus is a spread disease in the whole world and this study was conducted on Iraqi diabetic men to know the relation between type II diabetic and some prostate related markers including (prostate size, total prostate antigen, random blood sugar and zinc). Material and methods: This study included one hundred men their age ranges between (40-60 year), fifty males were suffering from type II diabetes mellitus, and other fifty men were non-diabetics. Some parameters such as (Prostate size, total prostate specific antigen (tPSA), random blood sugar (RBS) and Zinc (Zn+2) were studied. Results: The results have showed significant increase in prostate size 50.5000 ± 3.748 and random blood sugar 203.55 ± 13.629 mg/dl compared with non-diabetic group 39.650 ± 2.484 and 125.750 ± 5.396 mg/dl, respectively but there is non-significant difference in total prostate specific antigen 1.543 ± 0.087 ng/ml and zinc 9.725 ± 0.344 µmol/l in diabetic group compared with non-diabetic group 1.612 ± 0.152 ng/ml and 11.025 ± 0.582 µmol/l respectively at P≤0.05.Conclusions: Patients with type II diabetes mellitus are more liable to suffer from increase in prostate size and increase in RBS levels in Iraqi men under study.Keywords: Diabetic patient, Prostate size, RBS, Zinc and tPSA.